A comparison of individual and ecological indicators of social deprivation and their association with hospital efficiency in the context of infectious diseases in two French general paediatric departments. Issue 4 (27th January 2020) - Roussel, Aphaia; Faye, Albert; Lefevre-Utile, Alain; De Pontual, Loic; Chevreul, Karine; Michel, Morgane
Abstract: Background: To identify deprivation indicators usable in everyday practice and included in medico-administrative databases, particularly with infectious diseases, which represent the greatest proportion of hospitalizations. Our objective was to compare ecological indicators to individual questionnaires and apply both types to the study of the impact of deprivation on hospital efficiency. Methods: We conducted an epidemiological observational prospective multicentre study in two French public hospitals between 20 October 2016 and 20 March 2017. Children hospitalized for one of the four most common infectious diseases were included and their parents were asked to answer the Evaluation of Precarity and Inequalities in Health Examination Centers (EPICES) questionnaire. The ecological indicator French DEPrivation index (FDep) was derived from patients' address, both at the zip code and at a smaller geographical area (IRIS [ ilôts de regroupement pour l'information statistique ]) level. Correlation and concordance between the three indicators were assessed. The endpoint used to assess the impact on hospital efficiency was the ratio between patients' length of stay (LOS) and the national LOS of their disease-related group. Results: Data were available for 540 patients with a mean age of 9 mo. A total of 56.1% of patients were considered deprived with EPICES, 50.4% with zip code FDep and 45.7% with IRIS FDep. Concordance between EPICES and either type of FDep was <0.1. There was no increase in LOS compared with national LOS with any of the indicators. Conclusions: Individual and ecological indicators do not measure the same aspects of deprivation. The decision to use one or the other must be carefully weighed when studying the impact of deprivation on the healthcare system.